Algerian youth and sport’s information via Social Media A study on the effects of Facebook pages users’ - Dib, Youcef; Hadjam, Eldjemai (sports creativity, 2025)
The aim of the current study is to reval sport pages use by Algerian youth via Facebook social network , and its impacts, in order to highlight its cognitive, affective, and behavioral effects , outcoms of its usage.The study was based on two theoretical approaches, Gratification theory and Media Dependency theory. The survey was the followed method with the help of an electronic questionnaire distributed among 200 young Facebook sport pages users, selected according to a conveniance sample. The study results accentuated the fact that young Algerian users of Facebook sports pages spent a reasonable amounts of time and tend to prefer a stay alone use, and also they prefer posts containig Multimedia, and one of the effects also is they stay constantly tuned on sports news, and a way to vent and express their feeling and opinion and take part in sports debates